In Vivo Antihyperlipidemic Activity of TD.HLM01 – A Vietnamese Traditional Remedy in Experimental Models - Tung Thanh Tran; Ha Thi Thu Nguyen; Thuy Thanh Nguyen; Lien Huong Thi Nguyen; Van Hong Thi Nguyen; Hang Thi Thuy Nguyen; Quang Vinh Trinh; Hang Thi Thu Dinh; Duong Thuy Dau; Phong Xuan Pham; Nghia Trong Duong; Van Anh Thi Pham (Majalah Obat Tradisional, 2025)
One of the primary risk factors for cardiovascular disease nowadays is dyslipidemia. For many years, multi-herbal preparations have been the standard treatment approach for treating dyslipidemia. The purpose of this study was to assess the effects of TD.HLM01 hard capsule on experimental rodent models of endogenous and exogenous dyslipidemia. To create hyperlipidemia in the endogenous hyperlipidemia paradigm, mice were first given TD.HLM01 hard capsule therapy and intraperitoneal injections of poloxamer-407. In the exogenous model, rats were given a diet of oil-cholesterol mixture orally and treated with TD.HLM01 hard capsules for four consecutive weeks. Serum lipid parameters were evaluated in both experiments. The results indicated that TD.HLM01 significantly reduced TC, TG, and non-HDL-C levels in the experimental models of exogenous hyperlipidemia and endogenous hyperlipidemia. TD.HLM01 improved the serum LDH levels and ameliorated the elevated AST and ALT levels in cholesterol-induced hyperlipidemia rats. This study has demonstrated the potential efficacy of TD.HLM01 in hyperlipidemia experimental models in vivo.